Cystic Fibrosis Cases Missed by Newborn Bloodspot Screening—Towards a Consistent Definition and Data Acquisition - Anne Munck; Kevin W. Southern; Jared Murphy; Karin M. de Winter-de Groot; Silvia Gartner; Bülent Karadag; Nataliya Kashirskaya; Barry Linnane; Marijke Proesmans; Dorota Sands; Olaf Sommerburg; Carlo Castellani; et al. (International Journal of Neonatal Screening, 2023)
Repeated European surveys of newborn bloodspot screening (NBS) have shown varied strategies for collecting missed cases, and information on data collection differs among countries/regions, hampering data comparison. The ECFS Neonatal Screening Working Group defined missed cases by NBS as either false negatives, protocol-related, concerning analytical issues, or non-protocol-related, concerning pre- and post-analytical issues. A questionnaire has been designed and sent to all key workers identified in each NBS programme to assess the feasibility of collecting data on missed cases, the stage of the NBS programme when the system failed, and individual patient data on each missed case.